Теоретико-методичні підходи до аналізу доходів і витрат мисливських господарств України - Завадських, Ганна Миколаївна; Нехай, Вікторія Василівна; Zavadskykh, Hanna; Nekhai, Viktoriia (Запоріжжя : 2024, 2024)
UA: Розкрито сутність економічної діяльності мисливських господарств України в сучасних умовах Окреслено актуальність дослідження динаміки і структури доходів і витрат мисливських господарств України. Описано економічні та технологічні особливості мисливства як окремої галузі. Розкрито зміст понять «витрати» і «доходи мисливських господарств» та наведено їхнє трактування. Наведена класифікація та структура доходів і витрат мисливських господарств. Проаналізовано джерела доходів мисливських господарств та виявлено, що на їх функціонування впливає низка негативних факторів, які призводять до збитковості багатьох українських мисливських господарств. Оцінювання сучасного стану галузі показало, що для знаходження шляхів підвищення її ефективності необхідно провести комплексний моніторинг та системні дослідження проблем, що гальмують її розвиток. EN: Formulation of the problem. Income and expenditure research helps to understand the economic contribution of hunting to the regional economy and to develop strategies for its optimal use; hunting can have a major impact on the quality and lifespan of wild animals and their habitats. The purpose of the article. The purpose of the article is to substantiate the theoretical provisions and develop practical recommendations for improving the mechanism of income and expenditure formation of hunting farms of Ukraine. Presenting main material. The hunting industry is a separate sphere of the economy with its own economic and technological features. The income of hunting farms is a set of financial funds received by the owners and managers of hunting territories for the sale of products and services related to hunting activities. The costs of hunting farms are a set of monetary, material and labor resources that are consumed or spent to ensure the activities of hunting farms. Depending on how they are included in the cost of products or services, production costs can be classified as direct and indirect. Studies show that the total costs of running a hunting farm in Ukraine over the past 15 years have shown stable growth dynamics. Conclusions. In general, optimization of income and expenses of hunting farms of Ukraine requires a comprehensive approach taking into account various aspects of their activity and a balanced approach to the use of natural resources. In addition to their own financing, hunting farms need financial and legal support from the state based on the principles of the market economy.
The teoretical and methodological approaches to analysis of income and expenses of wildlife management enterprises in Ukraine
Keywords: витрати; доходи; собівартість; економічна оцінка; користувачі мисливських угідь; землі сільськогосподарського призначення; мисливські господарства; expenses; income; cost price; economic assessment; users of hunting grounds; agricultural land; wildlife management enterprises